An inter-site study of biofouling recruitment on static immersion panels in major ports of South East Asia and India - Chin Sing Lim; Zuliza Haji Jolkifli; Alina Jair; Noorizan Karim; Ranimah A. Wahab; Dattesh V. Desai; Venkat Krishnamurthy; Lidita Khandeparker; Kaushal Mapari; Subhash Sawant; Hikmah Thoha; Hadiyanto Hadiyanto; Dirhamsyah Dirhamsyah; Soukaseum Dalasane; Kongneun Chounlamountry; Lee Siang Hing; Shahruddin bin H. Yusof; Myint Myint Khaing; Hildie M. E. Nacorda; Nero Austero; Rhodora V. Azanza; Cesario Pagdilao; Sumana Kajonwattanakul; Ratchanee Puttapreecha; Sombat Poovachiranon; Hoang Mai Le; Thanh Thuy Tran; Van Cu Nguyen; Koh Siang Tan; Arga Chandrashekar Anil (ASEAN Journal on Science and Technology for Development, 2018)
Limited knowledge of native marine biodiversity hinders effective biodiversity management to safeguard South and Southeast Asia’s marine coastal environment against the threat of invasive species transfer through shipping. In particular, sessile marine biofouling organisms in South East Asian ports are poorly known. Through the support of the ASEAN-India Cooperation Project on the Extent of Transfer of Alien Invasive Organisms in South/South East Asia Region by Shipping, a coordinated effort to examine diversity of biofouling organisms in major port areas in Southeast Asia and India was made using polyvinylchloride (PVC) panels as recruitment surfaces in a static immersion study for a period of 12 months. Not surprisingly, the study revealed that fouling patterns differed between ports possibly as a result of dissimilar hydrographic conditions. However, there were also underlying similarities that reflected a regional uniformity in the composition of fouling communities. At the same time, the alien Caribbean bivalve Mytilopsis sallei was detected in Manila Bay (Philippines), Songkhla Port (Thailand) and Singapore. This is a first simultaneous biofouling survey involving scientists and government stakeholders from India and ASEAN nations of Brunei Darussalam, Indonesia, Lao PDR, Malaysia, Myanmar, Singapore, Thailand, Philippines and Vietnam.